PENGARUH E-WOM DAN E-PROMOTION TERHADAP KEPUTUSAN PEMBELIAN PRODUK DI TIKTOKSHOP - Febianti, Adiesty Nur; Inara Hilmi Arifah; Muhammad Nur Maulana; Ramayani Yusuf (Universitas Haji Sumatera Utara, 2024)
Abstract This research is focused on the city of Garut, where TiktokShop is present as an option for consumers to carry out online transactions. This study aims to show how the influence of E-WOM and e-Promotion relates to TiktokShop's purchasing decisions, influencing the level of purchasing decisions, by concentrating on the influence of E-WOM and e-Promotion. The results of the analysis show that E-WOM and E-Promotion simultaneously have an impact on the decision to make a purchase. The R2 value of 0.608 indicates that E-WOM and E-Promotion can explain 60.8% of the variability in purchasing decisions. The results of statistical tests show that, individually, E-WOM does not have a relatively significant impact on purchasing decisions.